An experimental and numerical investigation of different shear test configurations for sheet metal characterization - Yin, Qing; Zillmann, Benjamin; Suttner, Sebastian; Gerstein, Gregory; Biasutti, Manfredi; Tekkaya, A. Erman; Wagner, Martin F. -X.; Merklein, Marion; Schaper, Mirko; Halle, Thorsten; Brosius, Alexander (International Journal of Solids and Structures, 2014)
Simple shear tests are widely used for material characterization especially for sheet metals to achieve large deformations without plastic instability. This work describes three different shear tests for sheet metals in order to enhance the knowledge of the material behavior under shear conditions. The test setups are different in terms of the specimen geometry and the fixtures. A shear test setup as proposed by Miyauchi, according to the ASTM standard sample, as well as an in-plane torsion test are compared in this study. A detailed analysis of the experimental strain distribution measured by digital image correlation is discussed for each test. Finite element simulations are carried out to evaluate the effect of specimen geometries on the stress distributions in the shear zones. The experimental macroscopic flow stress vs. strain behavior shows no significant influence of the specimen geometry when similar strain measurements and evaluation schemes are used. Minor differences in terms of the stress distribution in the shear zone can be detected in the numerical results. This work attempts to give a unique overview and a detailed study of the most commonly used shear tests for sheet metal characterization. It also provides information on the applicability of each test for the observation of the material behavior under shear stress with a view to material modeling for finite element simulations. © 2013 Elsevier Ltd. All rights reserved.
LFT Import::2019-07-29 (1932)
Keywords: Heterogeneity; Sheet metal; Simple shear